Analisis pengaruh produk domestik regional bruto (PDRB) terhadap angka kemiskinan di Kabupaten Pemalang tahun 2003-2019 - Lestari, Desti Winda; N., Nolaika Arsiani; Sari, P. Puspita (Unnes Journal of Mathematics, 2021)
The purpose of this study is to determine the results of the analysis of the influence of Gross Regional Domestic Product (GRDP) on poverty rates in Pemalang District 2003-2019. The simple linear regression method is the method used in this study with the help of the Statictical Package for the Social Sciences (SPSS) software. The data used was obtained from the Badan Pusat Statistik (BPS) of Central Java Province with data on the percentage of poor people in Pemalang District as the dependent variable and GRDP data as independent variable. The results of this study indicate that the regression model has a match with the data, this means that the GRDP of poverty has a significant relationship and negatively affects the poverty rate, so the higher the GRDP value, the lower the poverty level. Therefore, through this research it is hoped that it can become a reference to the government in determining policies in an effort to increase growth and equitable development in Pemalang District in the future.